Extraction of Stevioside from Stevia Rebaudiana Leaves Using Cellulase - Nor Hayati, Shahidan (2012)
Stevioside is a diterpene glycoside present in Stevia Rebaudiana leaves that has the ability to sweeten at rated between 70 to 350 times than sucrose (0.4% w/v). It has no calorific value. Unlike many low calorie sweeteners, stevioside is stable at high temperature. The objective of this research is to extract stevioside from stevia rebaudiana leaves by using cellulase from Aspergillus Niger. Acetate buffer and ethanol were used as a medium for enzyme and as a solvent, respectively. In this present study, the enzymatic extraction of stevioside from stevia rebaudiana leaves was carried out using cellulase with various parameters that affect the production of stevioside such as concentration of enzyme, incubation time and temperature. Cellulase was observed to give the highest stevioside yield (16230 ± 0.3 μg/ml) at 40oC. This indicated that the maximum temperature for cellulase activity was 40oC. The results signify that the enzymatic extraction method is an alternative to solvent based stevioside extraction, based on its higher efficiency. Thus, it can be concluded that the extraction of stevioside from Stevia rebaudiana leaves using cellulase can be maximized under the maximum conditions for the cellulase activity where the used of solvent can be minimized in degrading the cell wall Together with the maximum heat and correct combination of the solvent used, a new and efficient way of extracting high yield of stevioside can be obtained.